Synthesis of Monolithic TiO2 Aerogels With Relatively Low Shrinkage and Improved Formability Assisted by CTAB - Niu, Tingting; Zhou, Bin; Zhang, Zehui; Yang, Jianming; Ji, Xiujie; Shen, Jun; Zhang, Zhihua; Du, Ai (Frontiers in Materials, 2021)
Monolithic TiO2 aerogels without severe shrink were obtained by the sol-gel method with the addition of the surfactant cetyltrimethylammonium bromide (CTAB) to control the hydrolysis and polycondensation process and acetonitrile solvent as the solvent to improve the crystallinity. After CO2 supercritical drying, the shrinkage ratio of monolithic TiO2 aerogels modified by CTAB decreased by up to ~26.9%, compared with the pure TiO2 aerogel. Their apparent densities were all lower than 300 g/cm3. X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and BET Specific Surface Area Analysis were used to analyze the as-synthesized samples. The results revealed that all the samples were anatase-TiO2 phase with nanoporous network structures. The specific surface areas reached 250.2 m2/g confirmed by the BET analysis. However, TiO2 aerogels without the addition of CTAB showed evident agglomeration and collapse of the network in comparison with CTAB-added samples. To further study the structure-property relationship, the photocatalysis performance of as-synthesized and 300 °C-calcined aerogels was carried out contrastively. Interestingly, the influences of the CTAB adding amount of as-synthesized and calcined TiO2 aerogels are negative and positive, respectively, which is probably due to the synergistic effect of CTAB hindrance and grain refinement. Potentially, CTAB-modified TiO2 aerogels with low density, less shrinkage, better formability, higher specific surface area and finer crystalline grain may be applied in various applications, such as electrochemistry, photocatalysis, etc.